Islamic Aesthetics in the Visual Branding of Padang Ampera Restaurants in Java - Gema Ariprahara; Sunarmi Sunarmi; Handriyotopo Handriyotopo (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2026)
Padang Ampera restaurants, as diaspora manifestations of Minangkabau culture in urban Java, do not merely display decorative visual elements for commercial attraction. Their logos, colors, spatial markers, ornaments, halal labels, and typographic choices function as a system of signs through which identity is communicated, negotiated, and legitimized This study integrates Islamic aesthetics to explain the ethical and formal boundaries of visual expression with cultural semiotics to interpret branding as a cultural text. To achieve this objective, a qualitative descriptive-analytical approach was implemented, involving field observations at 45 Padang Ampera restaurants across Bandung, Yogyakarta, and Malang, alongside in-depth interviews with 15 informants, including 5 owners and 10 patrons. These methods allow for a systematic decoding of how Minangkabau memory, Islamic values, and the social meaning of hospitality are materialized in contemporary commercial spaces. Through this combined framework, the branding of Padang Ampera restaurants can be understood not only as a marketing strategy but also as a signifying practice that transforms everyday commercial space into a visible expression of Muslim cultural identity. This article contributes to Islamic anthropology in at least three ways. First, it extends the discussion of Islam beyond ritual and doctrinal domains into the sphere of everyday material culture by showing how Islamic values are embodied in visual branding practices. Second, it demonstrates that restaurants can function as vernacular sites of religious-cultural expression, where design choices become a medium for articulating piety, propriety, and communal identity. Third, it highlights how Minangkabau migrants in Java negotiate continuity and adaptation through visual symbols that are both commercially effective and culturally meaningful. In this sense, the study offers a practical contribution by showing that branding in Muslim cultural enterprises may operate not only as an economic instrument but also as a medium of cultural transmission, identity preservation, and ethical representation in diaspora settings.